Development of a molecular platform for the detection and quantification of Newcastle vaccine virus - Ormeño Vásquez, Phillip (2018)
The objective of the study was to develop a molecular platform for the quantification of Newcastle disease virus (NDV) from a culture system in embryonated SPF eggs. First, four pairs of primers were evaluated that amplify different regions of the NDV viral genome that code for: nucleocapsid protein (NP), protein matrix (M), fusion protein (F) and RNA-dependent RNA polymerase (L) to select the most conserved one from which a molecular platform based on reverse transcription was developed - conventional polymerase chain reaction (RT-PCRc) in two steps for the detection of NDV. Subsequently, it was taken to reverse transcription - real-time polymerase chain reaction (RT-qPCR) for the quantification of NDV produced from a system of embryonated eggs. Through these techniques, it was determined that the primers for the M gene were adequate according to the optimization criteria for the development of both methods. Sensitivity tests showed that the RT-qPCR (116 genomic copies/μl) was 10 times more sensitive than the RT-PCRc. The primers proved to be specific since there were no amplifications in the negative controls or in other avian pathogens (infectious laryngotracheitis virus, avian metapneumovirus, infectious bronchitis virus, Avibacterium paragallinarum, Gallibacterium anatis and Ornithobacterium rhinotracheale). Due to its sensitivity and specificity, this platform is proposed for the quantification of NDV vaccine when it is produced from an embryonated egg system, as an alternative to conventional titration methods such as hemagglutination, plaque assay, TCDI50 and DIEP50.